Le Guyana: "Land of Six Peoples" ou "One People, One Nation" ? - Léna Loza (Anglophonia)
Guyana is referred to as both "Land of Six Peoples," a phrase extracted from the national anthem, or "One People, One Nation, One Destiny," the national motto. Using such opposite expressions to talk about one and the same country highlights meaningful divergences as regards Guyanese people’s viewpoints about what their society should be. Although top officials rejoice in the cohesiveness of Guyanese society, the latter is seemingly struggling to overcome the painful legacy of the colonial era. Examining postcolonial questions about Guyana entails transcending the traditional dichotomy "former colonizers/former colonized people." Indians and Blacks, who were both subject to colonial power, have indeed developed antagonistic relationships. In the face of a proclaimed unity which nevertheless fails to conceal real divisions, it is worth exploring what problems Guyanese society has faced since it gained independence in 1966 and what strategies it has resorted to in order to solve these issues